KARAKTERISTIK NYALA API PADA PEMBAKARAN SKALA MESO DENGAN TAMBAHAN SUDDEN EXPANSION DAN PLATE FLAME HOLDER - Mahendra Bagaskara (STATOR: Jurnal Ilmiah Teknik Mesin, 2022)
SUMMARY: Flame Characteristics In Meso Scale Combustion With The Addition Of Sudden Expansion And Plate Flame Holder; Mahendra Bagaskara, 181910101148; 2020; 206 pages; Department of Mechanical Engineering, Faculty of Engineering, University of Jember. The availability of the number of fossil energy sources or that cannot be renewed will be depleted on the surface of the earth, where the increasing growth in technology is one of the factors affecting the availability of energy sources. Due to supporting technology activities human in the present still use fossil fuels. The need for energy sources is so great but not matched by the amount of its availability in nature is the main factor for humans to start using energy sources whose availability will continue to exist if managed properly. One of the ways is by reducing the size of the combustion system and replacing fossil energy sources that originally used fuel oil to become natural gas (Ju and Maruta, 2011). The development in meso combustion is based on research by Wan Jian long (2018), which examines the use of a plate flame holder in the combustor section. This study resulted in a slightly different flame compared to the plate less mechanism. This has an effect on the residence time which can allow the reactants to be more mixed. This research was conducted with experimental where meso-scale combustor with sudden expansion added a flame holder in the form of a plate which is controlled by varying diameter outlet on the combustor. Of the two variations in thediameter outlet, namely 8 mm and 10mm, the results show that at conditions of equivalent ratio (Ф) = 1, the combustor 10 mm has a better flammability limit, more stable fire, and shape of the fire tends to widen and forms like 2 letter c or a semicircle in the plate holder.